2014
DOI: 10.3109/00207454.2014.909415
|View full text |Cite
|
Sign up to set email alerts
|

Does fatigue occur in MS patients without disability?

Abstract: Fatigue occurs in patients with MS in the absence of motor dysfunction and is associated with the disease itself, the sedentary lifestyle, and mood disorders. The 6MWT is not useful to demonstrate motor fatigue in subjects without neurological disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 35 publications
3
15
0
Order By: Relevance
“…In our study we ob tained sim i lar re sults -27.9% of MS pa tients were de pressed. An as so ci a tion between fa tigue and de pres sion was found, sim i lar to the results ob tained in other stud ies that showed cor re la tion between de pres sion and fa tigue [33,34,36,37,40,41]. Depres sive symp toms in crease the fa tigue ei ther di rectly or as a re sult of its psy cho log i cal con se quences [42][43][44][45].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In our study we ob tained sim i lar re sults -27.9% of MS pa tients were de pressed. An as so ci a tion between fa tigue and de pres sion was found, sim i lar to the results ob tained in other stud ies that showed cor re la tion between de pres sion and fa tigue [33,34,36,37,40,41]. Depres sive symp toms in crease the fa tigue ei ther di rectly or as a re sult of its psy cho log i cal con se quences [42][43][44][45].…”
Section: Discussionsupporting
confidence: 85%
“…Neu ro log i cal dis abil ity mea sured by EDSS was also strongly re lated to fa tigue in other stud ies [30][31][32][33][34][35]. But there are stud ies which dem on strate that percep tion of fa tigue oc curs in MS in de pend ently of the neu rolog i cal im pair ment [36][37][38]. We should con sider that as sessing ce re bral func tional sys tem score which is a part of EDSS, fa tigue is al ready eval u ated on a scale from 0 to 3.…”
Section: Discussionmentioning
confidence: 91%
“…The distanced walked by nonfatigued group was significantly higher than in fatigued group. Although some previous studies found no correlation between EDSS scores and the levels of perceived fatigue and that fatigue appears because of mood, sleep disorders, and low levels of physical activity in the absence of gait alterations (Alvarenga‐Filho et al, ). Further research on how to assess motor fatigue and on how to establish the reason why this may be related to neurological impairment and gait alterations in MS patients is required.…”
Section: Discussionmentioning
confidence: 92%
“…This may explain the differences observed in our study between the mild group and the healthy group. Nevertheless, other studies have not reported fewer distances walked during performance of the 6MWT in PwMS, and they suggest that this test is inappropriate for detecting or inducing motor fatigue in MS patients with EDSS ≈ 1 (Alvarenga‐Filho et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple sclerosis (MS) is a neurological disorder that compromises the integrity of signaling pathways in the central nervous system through chronic inflammatory responses and neurodegeneration ( Trapp and Nave, 2008 ). Although the clinical progression of MS varies widely between individuals ( Lublin and Reingold, 1996 ; Confavreux and Vukusic, 2006 ), one of the most common symptoms of the disease is a heightened level of fatigue ( Fisk et al, 1994 ; Alvarenga-Filbo et al, 2015 ; Loy et al, 2017 ; Penner and Paul, 2017 ), the underlying mechanisms of which are poorly understood.…”
Section: Introductionmentioning
confidence: 99%